Behavioral Impulsivity Does Not Predict Naturalistic Alcohol Consumption or Treatment Outcomes. (September 2016) - Mullen, Jillian; Mathias, Charles W.; Karns, Tara E.; Liang, YuanYuan; Hill-Kapturczak, Nathalie; Roache, John D.; Lamb, R. J.; Dougherty, Donald M.
Abstract : Objective: The purpose of this study was to determine whether behavioral impulsivity under multiple conditions (baseline, after alcohol consumption, or after serotonin depletion) predicted naturalistic alcohol use or treatment outcomes from a moderation-based contingency management (CM) intervention. Method: The current data analysis pulls information from 3 phases of a large study: (1) phase 1 examined baseline and the effects of alcohol use and serotonin depletion on 3 types of behavioral impulsivity: response initiation (IMT task), response inhibition (GoStop task), and delay discounting (SKIP task); (2) phase 2 involved 28 days of naturalistic drinking; and (3) phase 3 involved 3 months of CM. During phases 2 and 3 alcohol use was measured objectively using transdermal alcohol monitors. The results of each individual phase has been previously published showing that at a group level the effects of alcohol consumption on impulsivity were dependent on the component of impulsivity being measured and the dose of alcohol consumed but serotonin depletion had no effect on impulsivity, and that a moderation-based CM intervention reduced heavy drinking. Results: The current analysis combining data from those who completed all 3 phases (n=67) showed that impulsivity measured at baseline, after alcohol consumption, or after serotonin depletion did not predict naturalistic drinking or treatment outcomes from a moderation-based CM treatment. Conclusions: CM interventions may prove to be an effective intervention for impulsive individuals; however, normal variations in measured impulsivity do not seem to relate to normal variations in drinking pattern or response to moderation-based CM.